Survival trends of gastrointestinal stromal tumor in real-world settings: a population-based retrospective study - Guohua Jia; Xiangpan Li (Pathology and Oncology Research)
PurposeThis study aims to evaluate whether survival outcomes for GIST patients have improved over the past decades and to identify the specific patient subgroups that have benefited from advances in treatment.Patients and methodsA total of 4,127 GIST patients diagnosed between January 1980, and December 2019, were included in this study using data from the Surveillance, Epidemiology, and End Results (SEER)-9 Registries. Survival differences among GIST patients were analyzed across five time periods (1980–1999, 2000–2004, 2005–2009, 2010–2014, and 2015–2019) and within demographic, neoplastic, temporal, economic, and geographic categories using the log-rank test. Multivariable Cox regression models were employed to identify risk factors associated with GIST-specific survival. Associations between time periods and GIST-specific mortality (TSM) were examined using a multivariable Cox regression model.ResultsSurvival outcomes for GIST patients significantly improved in the 2000–2009 period but showed no substantial improvement in the 2010–2019 period. After adjusting for age, gender, tumor location, ethnicity, tumor stage, median household income, and geographic area, the multivariable Cox regression models revealed that older age (≥65 years) (HR = 1.977, 95% CI = 1.470–2.657), tumors located outside the gastrointestinal tract (HR = 1.505, 95% CI = 1.267–1.786), regional lesions (HR = 2.225, 95% CI = 1.828–2.708), and distant lesions (HR = 5.177, 95% CI = 4.417–6.069) were independent risk factors for TSM (p < 0.05). After adjusting for time periods and age, gender, tumor location, tumor stage, median household income, patients in 2000–2004 (HR = 0.662, 95% CI = 0.523–0.839), 2005–2009 (HR = 0.431, 95% CI = 0.339–0.549), 2010–2014 (HR = 0.437, 95% CI = 0.341–0.561), and 2015–2019 (HR = 0.365, 95% CI = 0.273–0.489) had a significantly lower risk of TSM than patients in 1980–1999 (p < 0.05). Similarly, patients in 2005–2009 (HR = 0.661, 95% CI = 0.555–0.788), 2010–2014 (HR = 0.696, 95% CI = 0.578–0.838), and 2015–2019 (HR = 0.607, 95% CI = 0.476–0.773) also had a significantly lower risk of TSM than patients in 2000–2004 (p < 0.05). However, patients in 2010–2014 (HR = 1.042, 5% CI = 0.863–1.258) and 2015–2019 (HR = 0.945, 95% CI = 0.734–1.216) did not have a significantly lower risk of TSM compared to patients in 2005–2009 (p > 0.05).ConclusionGIST survival has significantly improved during the period 2000–2009 but showed no substantial improvement in 2010–2019, with the turning point for lower risk of TSM being 2005. Innovative strategies are needed to further improve survival outcomes for GIST patients, particularly for older patients and those with tumors originating outside the gastrointestinal tract.